Deontological aspects of the amyotrophic lateral sclerosis - T. M. Alekseeva; V. S. Demeshonok; S. N. Zhulev (Нервно-мышечные болезни)
One of the significant problems in deontology is the degree of awareness of terminally ill patients regarding the diagnosis and prognosis of their disease. This topic is complex and relevant, it touches ethical and psychological, legal and medical aspects. The article discusses the positive and negative aspects of fully informing patients  with amyotrophic lateral sclerosis about the fatal diagnosis. There are 2  clinical cases reflecting different approaches of this complex issue: full awareness and concealment of the diagnosis.